Introductory discrete mathematics - Rhoades, Christopher (Wiilford Press, 2018)
Discrete mathematics is defined as the study of mathematical structures which are not continuous. This includes integers, statements in logic, graphs, etc. The most important concepts studied under this subject are number theory, logic, probability, graph theory, algebra, set theory, information theory, combinatorics, geometry, game theory, topology, etc. This book provides comprehensive insights into the field of discrete mathematics. It aims to shed light on some of the unexplored aspects of the area. Different approaches, evaluations and methodologies have been included in the text. This book is an essential guide for both academicians and those who wish to pursue this discipline further.